Advertisements
Advertisements
Question
Without using truth table, prove that:
[p ∧ (q ∨ r)] ∨ [∼r ∧ ∼q ∧ p] ≡ p
Sum
Solution
LHS = [p ∧ (q v r)] ∨ [∼r ∧ ∼q ∧ p]
≡ [p ∧ (q ∨ r)] ∨ [(∼r ∧ ∼q) ∧ p] ... (Associative Law)
≡ [p ∧ (q ∨ r)] ∨ [(∼q ∧ ∼r) ∧ p] ... (Commutative Law)
≡ [p ∧ (q ∨ r)] ∨ [∼(q ∨ r) ∧ p] ... (De Morgan’s Law)
≡ [p ∧(q ∨ r)] ∨ [p ∧ ∼(q ∨ r)] ... (Commutative Law)
≡ p ∧ [(q ∨ r) ∨ ∼(q ∨ r)] ... (Distributive Law)
≡ p ∧ t ... (Complement Law)
= RHS
shaalaa.com
Is there an error in this question or solution?